The importance of daily care in skin health (Research, Society and Development, 2023)
Skin is considered to be one of the largest organs in the body and protects against chemicals, physical products, bacteria, fungi, and the sun's rays. Skin care is essential for the prevention of diseases such as skin cancer. Besides several products for cleaning and moisturizing, other cares such as a good night's sleep, healthy eating, and water consumption can contribute to prevent premature aging. There are several types of skin, such as oily, normal, dry, mixed, and sensitive. Still, to perform the daily skin care it is essential to choose a suitable routine for your skin, because an inappropriate use of products can worsen skin health. The purpose of the research is to describe what skin is, informing its layers, what types of skin and what care for each type and what can be caused by a lack of care. The research was conducted through a systematic review of literature in materials published in databases, and the results will be presented in tables and texts with citations. The habit of taking care of the skin should be part of the routine of men and women of all ages, not only for aesthetic purposes, but also for the sake of a healthy life.